English corpus linguistics crossing paths - Kytö, Merja (Language and computers, 2012)
The chapters in this collected volume illuminate the dynamic success story of English corpus linguistics over the past few decades. The book is organised in three parts. The chapters in Part I set the scene by addressing fundamental issues such as the balance between automated and manual analyses, and the urgent call for more communication and collaboration across subjects and research areas. The studies in Part II highlight patterns in Present-day English from a cross-linguistic perspective, and identify and analyse stylistic trends in recent English. Part III is devoted to aspects of the ric.